Individual adaptation to climate change: The role of information and perceived risk - Daniel Osberghaus; Elyssa Finkel; Max Pohl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Given that many of the predicted effects of climate change are considered imminent and unavoidable, the need to mainstream adaptation as a viable coping measure among private households is becoming a topic of increasing importance. However, little research to date has assessed the factors influencing the motivation to autonomously adapt, nor any successful measures for instigating this behavioural change. This study investigates whether providing locally-focused vs. globally-focused information about the effects of climate change influences the personal perceived risk (PPR) of individual people. Based on a socio-psychological model, Protection Motivation Theory (PMT), it is hypothesized that a higher PPR will lead to a higher motivation to adapt. While this hypothesis has been empirically confirmed by the study, it has been found that providing information on climate change effects that is more personally relevant to the individual and is concerned with his local surroundings does not significantly increase PPR. This may be due to a trade-off between spatial-temporal distance and the comparably low severity of predicted effects in the study region. Interestingly, providing any kind of information, irrespective of having a global or local focus, also did not increase PPR as compared to receiving no information. These results suggest that the sole provision of information about expected climate change impacts, even if tailored to one's individual context, does not significantly increase PPR and consequently the motivation to adapt. Another necessary factor might be increasing the knowledge about concrete coping options to allow people to weigh up their personal options.
Keywords: Q54; Q58; D83; 330; Klimaveränderung; Verhaltensökonomik; Anpassung; Motivation; Risiko; Informationsverhalten; Wahrnehmung